Impact of covid-19 pandemic on nationwide antidiabetic drug utilization - TAZEGÜL, GÖKHAN; AKICI, AHMET (My University, 2023)
Introduction The COVID-19 pandemic resulted in various outcomes that have altered disease prevalence and drug utilization patterns. Our study aimed to evaluate the trends in the utilization and costs of antidiabetic medications before and during the COVID-19 outbreak in Turkey. Methods We obtained nationwide sales data for antidiabetics from IQVIA Turkey, spanning between April 2018 and March 2022. Mean monthly drug utilization and expenditure trends before the pandemic (April 2018-March 2020) and during the pandemic (April 2020-March 2022) were compared. Drug utilization was measured by defined daily dose/1000 inhabitants/day (DID) unit. Results Utilization of antidiabetic drugs increased significantly from 125.7G12.5 DID before the pandemic to 158.3G25.7 DID during the pandemic (P! 0.001). There was a considerable rise in the use of oral antidiabetics, with utilization increasing from 71.2G6.9 DID prior to the pandemic to 90.6G17.2 DID (P! 0.001). Moreover, insulins and their analogs were utilized more frequently during the pandemic, rising from the pre-pandemic levels of 52.4G6.7 DID to 65.4G10.0 DID (P! 0.001). Marked increases were observed in the expenses for antidiabetics, moving from 65.4G8.4 to 86.7G15.0 million Euros (P! 0.001). These increments were noted both for oral antidiabetics (from 35.8G5.6 to 50.4G10.2 million Euros, P! 0.001) and insulins (from 27.1G3.7 to 33.4G5.7 million Euros, P! 0.001). Conclusion Our study demonstrated a surge in the utilization and expenditure of antidiabetics in the two years of the COVID-19 pandemic in Turkey, compared to prepandemic levels. These results should be considered in evaluating the association of COVID-19 infection with chronic diseases such as diabetes, as well as the outcomes of interventions to facilitate access to drugs for extraordinary circumstances.